Viewing arthrography images affects treatment preferences for Legg-Calvé-Perthes disease among medical professionals. - Kacmaz, Ismail Eralp; Reisoglu, Ali; Basa, Can Doruk; Zhamilov, Vadym; Agus, Haluk (Journal of Orthopaedics, 2020)
We explored how experience of arthrography affects treatment preferences for Legg-Calvé-Perthes disease (LCPD) patients. We also examined changes in surgical procedure preferences after examining arthrography images. In addition, we analysed the effect of experience with arthrography on treatment and surgical modality preferences. A case-based questionnaire was completed by 26 participants. Information on age, symptoms, hip range of motion (ROM), and extremity length differences were provided for eight LCPD cases. Based on these data and roentgenography images of the cases, the respondents were questioned regarding diagnostic, treatment, and surgical preferences. A slide was shown of arthrography images of each case and the same questions were asked to determine any changes in treatment preferences. The participants were divided into arthrography-experienced (Group 1, n = 16) and -inexperienced (Group 2, n = 10) groups to determine differences in treatment preferences in association with experience. After the participants had examined the arthrography images, a significant decrease in the number of additional examination requests was observed (p < 0.001). A significant group difference was also found in the rate of change of preference in diagnostic modality (p < 0.001). After arthrography images were examined, the tendency towards a preference for surgery increased in all participants. However, no significant difference between the experience groups was observed (p = 0.193). In addition, after arthrography images were examined, there was an increased tendency towards a preference for femoral valgisation and Salter osteotomy among participants who chose surgical treatments (p = 0.408). The treatment preferences difference between the two experience groups were not significant, and nor was the preference regarding surgical procedures (p = 0.999). Previous studies have shown that arthrography is useful for planning treatment and informing decisions regarding surgical modality for LCPD. However, no study has explored changes in treatment preferences after viewing arthrography images. This study explored such changes in choices regarding the diagnostic method and treatment modality. Our study showed that experience with arthrography decreased the preference for additional diagnostic tests (p < 0.001). Experience of arthrography increased the preference for surgery, though not significantly (p = 0.193).